2021
DOI: 10.3390/ijms22136703
|View full text |Cite
|
Sign up to set email alerts
|

Do Changes in ACE-2 Expression Affect SARS-CoV-2 Virulence and Related Complications: A Closer Look into Membrane-Bound and Soluble Forms

Abstract: The SARS-CoV-2 virus utilizes angiotensin converting enzyme (ACE-2) for cell entry and infection. This enzyme has important functions in the renin-angiotensin aldosterone system to preserve cardiovascular function. In addition to the heart, it is expressed in many tissues including the lung, intestines, brain, and kidney, however, its functions in these organs are mostly unknown. ACE-2 has membrane-bound and soluble forms. Its expression levels are altered in disease states and by a variety of medications. Cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 99 publications
0
21
0
Order By: Relevance
“…This region is reported to be the most essential for viral attachment and entry into the host cells [44,45]. Therefore, ACE2 expression in different tissues and interactions with SARS-CoV-2 are critical for the infection's progression to severe coronavirus disease 2019 (COVID-19) [46]. The P314L mutation in NSP12 (RNA-dependent polymerase) may play a causal role in viral replication, therefore enhancing its transmission ability and infectivity [44].…”
Section: Discussionmentioning
confidence: 99%
“…This region is reported to be the most essential for viral attachment and entry into the host cells [44,45]. Therefore, ACE2 expression in different tissues and interactions with SARS-CoV-2 are critical for the infection's progression to severe coronavirus disease 2019 (COVID-19) [46]. The P314L mutation in NSP12 (RNA-dependent polymerase) may play a causal role in viral replication, therefore enhancing its transmission ability and infectivity [44].…”
Section: Discussionmentioning
confidence: 99%
“…Following this pre-incubation, the cells were treated with the same compound dilutions in MEM medium containing only 1% FCS, to prevent the inhibition of infection by components of FCS [ 12 ]. Moreover, soluble ACE2 can effectively block the binding of SARS-CoV S-protein to membrane-bond ACE2 and thereby prevents SARS-CoV entry [ 13 , 14 ], which is possibly transferable to SARS-CoV-2. Since FCS contains soluble ACE2, a reduced FCS concentration possibly intensifies the infection of Caco-2 cells [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, others suggested that sACE2 might reduce the infection success of SARS-CoV-2 [ 15 ]. The multilevel interactions of ACE2 with SARS-CoV-2 -protein have been reviewed recently [ 16 ].…”
Section: Introductionmentioning
confidence: 99%